(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Supplementation is one of the methods to optimize the intake of nutritional needs, especially with more specific goals. Amino acid supplementation is becoming popular among athletes and sports enthusiast. Consumption of amino acid supplementation by these groups has several purposes, including preventing deficiency, improving muscle function, and preventing muscle damage – which in turn can optimize performance during exercise. Looking at the role in body metabolism, amino acid anabolism can form various components such as hormones, enzymes, neuromodulators, and structural functions such as skeletal muscle that are related to sports performance. Amino acid catabolism is also known to form a substrate for gluconeogenesis that allows use during exercise. Based on this, is it true that amino acid supplementation can have a positive effect on exercise performance? It turns out that there are still several contradictory studies related to the effects of amino acid supplementation. Among the many amino acids, a meta-analysis review demonstrated positive effects for branched chain amino acids (BCAAs), β-alanine, and arginine on exercise performance. More studies are needed, both experimental and meta-analytical reviews to prove how other amino acids play a role in sports performance.